Upaya Peningkatan Minat Literasi Siswa melalui Kegiatan Ekstrakurikuler Tuntas Baca di SMP Swasta IRA Medan - Syarifah Widya Ulfa; M. Aulia Fadlan Aminullah; Rini Angraini; Dwi Sekar Andini; Devi Oktaviani Putri (Journal on Education, 2023)
Literacy is a crucial foundation in students' lives. This literacy is not confined to a classroom. These skills can also be acquired from outside the classroom. One is extracurricular activities. The purpose of this study is to know efforts to increase literacy interest in students. The study involves qualitative methods. Studies have shown a slow increase in after-school activities by completed extracurricular reading at SMP Swasta IRA. However, the changes have not been able to improve literacy interest well. There are still many students who have not yet recognized the importance of literacy. In this regard, teachers should give more encouragement to overcome them.